2017
DOI: 10.1007/s11548-017-1641-2
|View full text |Cite
|
Sign up to set email alerts
|

Retrospective evaluation and SEEG trajectory analysis for interactive multi-trajectory planner assistant

Abstract: Our approach improved manual planned trajectories in 98% of cases in terms of quantitative indexes, even when applying more conservative criteria with respect to actual clinical practice. The improved multi-trajectory strategy overcomes the previous work limitations and allows electrode optimization within a tolerable time span.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 21 publications
(23 citation statements)
references
References 31 publications
0
23
0
Order By: Relevance
“…Using this platform, the surgeon was able to select the desired entry and target points in~60 s and overall planning time was reduced to~5 min. As computer processing power has increased multimodal image registration [33], automated segmentation [34] and 3D rendering [35] have allowed neurosurgical planning to become quicker and more sophisticated.…”
Section: Laser Interstitial Thermal Therapymentioning
confidence: 99%
“…Using this platform, the surgeon was able to select the desired entry and target points in~60 s and overall planning time was reduced to~5 min. As computer processing power has increased multimodal image registration [33], automated segmentation [34] and 3D rendering [35] have allowed neurosurgical planning to become quicker and more sophisticated.…”
Section: Laser Interstitial Thermal Therapymentioning
confidence: 99%
“…Abhinav et al presented the technological advances leading up to the development of DTI and more advanced techniques aimed at imaging the white matter (Thomas et al, 2014). Different automatic algorithms have been proposed for minimally invasive neurosurgery, mainly for Stereoelectroencephalography (SEEG), Deep Brain Stimulation (DBS) and needle biopsies with the main goal of assisting the surgeon during the planning phase (Scorza et al, 2017).…”
Section: Related Workmentioning
confidence: 99%
“…• The percentage of CTs and RTs that did not exceed θ max =30 • , defined as the maximum insertion angle with respect to skull normal acceptable for electrode placement (Scorza et al, 2017), as described in Equation 15and shown in Figure 3B.…”
Section: Validation Of Rts Vs Ctsmentioning
confidence: 99%
“…Essert et al [3] formalized the implicit and explicit principles used by surgeons in DBS manual planning to tune an automatic straight trajectory planner. A multi-planner for Stereoelectroencephalography (SEEG) solution proposed in [5] (subsequently improved in [13]) is able to provide the surgeon with the best configuration for multiple linear electrodes, accounting for the spacial relationships among them. This is also obtained by expanding each EP initially selected by the surgeon to an entry area, where new EPs are estimated in order to search for novel trajectories.…”
Section: Related Workmentioning
confidence: 99%
“…Simulation parameters and hard constraints values are reported in Table I. The values of the maximum inclination angle α max and M entry radius were consistent with those used in [13], while the minimum distance d pp between adjacent COMs was defined as a reasonable value in accordance with the resolution of the MRI data. The test demonstrated a saturation in the number of COMs obtained by mesh decimation and the data showed a good fit with an exponential trend (R-square= 0.986), thus an optimal decimation value has been defined as ξ opt = 70%.…”
Section: A Decimation Thresholdmentioning
confidence: 99%